2020
DOI: 10.1002/cctc.202001799
|View full text |Cite
|
Sign up to set email alerts
|

Selective C−O Bond Cleavage of Bio‐Based Organic Acids over Palladium Promoted MoOx/TiO2

Abstract: Hydrodeoxygenation chemistries play a key role in the upgrading of biomass‐derived feedstocks. Among these, the removal of targeted hydroxyl groups through selective C−O bond cleavage from molecules containing multiple functionalities over heterogeneous catalysts has shown to be a challenge. Herein, we report a highly selective and stable heterogeneous catalyst for hydrodeoxygenation of tartaric acid to succinic acid. The catalyst consists of reduced Mo5+ centers promoted by palladium, which facilitate selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Interestingly, 3-hydroxytetrahydrofuran was not observed as a reaction intermediate even at very low conversions (<10%), suggesting that OH removal was not sequential. However, this behavior is substrate-structure-dependent, since in our prior studies we showed that tartaric acid conversion over similar catalytic systems proceeded through sequential C–O bond cleavage …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Interestingly, 3-hydroxytetrahydrofuran was not observed as a reaction intermediate even at very low conversions (<10%), suggesting that OH removal was not sequential. However, this behavior is substrate-structure-dependent, since in our prior studies we showed that tartaric acid conversion over similar catalytic systems proceeded through sequential C–O bond cleavage …”
Section: Resultsmentioning
confidence: 97%
“…Monometallic catalysts MoO x /TiO 2 (2 wt % Mo) and Pd/TiO 2 (0.3 wt % Pd) were prepared by incipient wetness impregnation of aqueous solutions of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O and Pd­(NO 3 ) 2 ·2H 2 O on TiO 2 (P25) as reported previously by Nacy et al Monometallic catalysts were then dried overnight at 393 K and calcined in air at 773 K for 3 h. The MoO x -M/TiO 2 (2 wt % Mo, M/Mo molar ratio = 0.14) catalysts with varying hydrogen dissociating metal (M = Pd, Pt, Rh) were prepared by incipient wetness impregnation of aqueous solutions of Pd­(NO 3 ) 2 ·2H 2 O, H 2 PtCl 6 ·6H 2 O, and RhCl 3 · x H 2 O on TiO 2 (P25); followed by drying at 393 K for 12 h. The samples were then impregnated with an aqueous solution of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, dried at 393 K for 12 h, and calcined in air at 773 K for 3 h. For supported catalyst M′O x -Pd/TiO 2 (2 wt % M′, Pd/M′ molar ratio = 0.14) with varying oxophilic metals (M′ = Mo, Re, W), an aqueous solution of Pd­(NO 3 ) 2 ·2H 2 O was deposited by incipient wetness on TiO 2 (P25), then dried at 393 K for 12 h. The dried powders were then impregnated with (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, NH 4 ReO 4 , and (NH 4 ) 10 W 12 O 41 · x H 2 O; dried at 393 K for 12 h; and calcined in air at 773 K for 3 h. Catalysts with varying supports were prepared by incipient wetness impregnation of aqueous solutions of Pd­(NO 3 ) 2 ·2H 2 O on TiO 2 (P25), ZrO 2 , γ-Al 2 O 3 , and SiO 2 . After drying the samples at 393 K for 12 h, an aqueous solution of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O was deposited by incipient wetness impregnation prior to calcination in air at 773 K for 3 h. Metal loadings on the catalyst with varying supports was 0.3 wt % Pd and 2 wt % Mo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pagán-Torres et al have very recently reported that MoO x –Pd/TiO 2 catalyzes the reduction of tartaric acid to succinic acid which is the product of DODH + hydrogenation with H 2 as a reducing agent; however, the proposed main reaction pathway is successive C–O bond cleavage via malic acid rather than DODH + hydrogenation. 55 Heyden et al have recently suggested that monomeric Mo species on TiO 2 can work as a DODH catalyst with a DFT-calculated free energy barrier of 1.5 eV at the C–O bond dissociation step. 56 In this study, we investigated the catalysis of MoO x –Au/TiO 2 for the reduction of polyols with H 2 as a reducing agent.…”
Section: Introductionmentioning
confidence: 99%